1991
DOI: 10.1016/s0022-5347(17)38074-6
|View full text |Cite
|
Sign up to set email alerts
|

Familial Patterns of Prostate Cancer: A Case-Control Analysis

Abstract: Epidemiological data have not yet enabled physicians to look beyond age and race to identify men at increased risk for prostate cancer. We conducted a hospital-based case-control study of familial patterns of prostate cancer with self-reported data from a risk-factor questionnaire. There were 385 patients with histologically confirmed prostate cancer, and 385 race and age-matched (+/- 5 years) controls with other cancers. Family history, available for 378 patients and 383 controls, was positive for prostate ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
1
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(75 citation statements)
references
References 10 publications
1
72
1
1
Order By: Relevance
“…22 These risk estimates are substantially lower than those from casecontrol studies, which ascertained data on family history retrospectively and may have overestimated risk. [23][24][25][26][27] Given that family history reflects not only shared genes but also shared environments and common behaviors, 14 lower risk estimates could in part result from less variability in the latter factors, particularly in a relatively homogeneous population such as in the present study. In this regard, it is interesting to note that having a family history of other cancers that do share some of the same risk factors with prostate cancer (i.e., red meat consumption with colorectal cancer) 28,29 was not associated with prostate cancer risk in our study, although 1 study reported that family history of breast cancer was associated with a prostate cancer relative risk of 1.7.…”
Section: Discussionmentioning
confidence: 80%
“…22 These risk estimates are substantially lower than those from casecontrol studies, which ascertained data on family history retrospectively and may have overestimated risk. [23][24][25][26][27] Given that family history reflects not only shared genes but also shared environments and common behaviors, 14 lower risk estimates could in part result from less variability in the latter factors, particularly in a relatively homogeneous population such as in the present study. In this regard, it is interesting to note that having a family history of other cancers that do share some of the same risk factors with prostate cancer (i.e., red meat consumption with colorectal cancer) 28,29 was not associated with prostate cancer risk in our study, although 1 study reported that family history of breast cancer was associated with a prostate cancer relative risk of 1.7.…”
Section: Discussionmentioning
confidence: 80%
“…3,11,12 Men with a family history of prostate cancer have a higher risk of prostate cancer, and this is reflected in the high percentage of GPs in our study who PSA test men who have a relative with prostate cancer. 13 The frequency with which screening is performed was not formally assessed in our study. Screening is often carried out on an annual basis, but recent analysis has suggested that screening every 2 y may be sufficient.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies (Steinberg et al, 1990;Spitz et al, 1991) reported a higher rate of prostate cancer in family members of cases than in family members of controls. In our study, the difference in the number of brothers affected by the same malignant tumour could be the result of cases having more brothers than controls, although fathers, grandfathers and sons of cases more frequently had prostate cancer than the same relatives of controls; because the case group was not large enough, this association was not found to be an independent one.…”
Section: Methodsmentioning
confidence: 99%